Malay language as a foreign language and the Singapore’s education system - Aishah Md Kassim, (Penerbit UKM, 2008)
The paper highlights the impact of the Singapore’s bilingual education policy on the Malay language and how the language has been regarded a foreign language in the Singapore context given the interest of policy makers in the implementation of a new third language policy. The growth can be hampered, however, to some concerns arising from the bilingual policy namely inadequate manpower, teaching materials, lack of resources and opportunities for using the language.